Double burden of malnutrition and its associated factors among adolescents in Debre Berhan Regiopolitan City, Ethiopia: a multinomial regression model analysis - Getacher, Lemma; Ademe, Beyene Wondafrash; Belachew, Tefera (Frontiers in Nutrition, 2023)
The double burden of malnutrition (DBM), contained both undernutrition and overnutrition, is a growing public health concern that presents a significant challenge to the food and nutrition policies of developing nations such as Ethiopia. However, the prevalence and contributing factors of DBM among adolescents in the study area have not been adequately investigated by Ethiopian researchers. Therefore, this study aims to determine the prevalence of DBM and contributing factors among secondary school students in Debre Berhan City, Ethiopia.A school-based cross-sectional study was conducted among 742 adolescents aged 10-19 years from September 28, 2022, to November 01, 2022, using a multi-stage sampling method. Data were collected using the online Kobo toolbox tool. A multinomial logistic regression model was used to analyze the data. The data were cleaned and analyzed in R software 4.2.2. Adolescents who had body mass index for age Z score (BAZ) <-2 SD, > +1 SD, and > +2 from the median value were considered thin, overweight, and obese, respectively.The overall prevalence of DBM was 21.5% (14.8% thinness and 6.7% overweight/obesity). In the multivariable multinomial logistic regression analysis models factors such as age [(AOR=0.79, 95% CL: (0.67, 0.93)], sex [(AOR=3.86, 95% CL: (2.35, 6.32)], school type [(AOR 5.03, 95% CL: (2.30, 10.99)], minimum dietary diversity score [(AOR=2.29, 95% CL: (1.27, 4.14)], frequency of meals [(AOR=2.09, 95% CL: (1.13, 3.89)], home gardening practice [(AOR=2.31, 95% CL: (1.44, 3.67)], history of illness [(AOR=0.57, 95% CL: (0.36, 0.93)], and knowledge of nutrition [(AOR=4.96, 95% CL: (1.61, 15.33)] were the significant predictors of either thinness or overweight/obesity (DBM).More than one-fifth of adolescents were affected by DBM in the study area. This prevalence is higher compared with the national and regional prevalence that found to be a public health concern. Thus, interventions like double-duty interventions should consider the age, sex, school type, minimum dietary diversity score, frequency of meals, home gardening practice, history of illness, and nutritional knowledge of adolescents.